The UK National External Quality Assessment Scheme for Heritable Bleeding Disorders - Perry, David J.; Cumming, Tony; Goodeve, Anne; Hill, Marian; Jennings, Ian; Kitchen, Steven; Walker, Isobel (Seminars in Thrombosis and Hemostasis, 2014)
Molecular genetic analysis of families with hemophilia and other heritable bleeding disorders is a frequently requested laboratory investigation. In the United Kingdom, laboratories undertaking genetic testing must participate in a recognized external quality assessment scheme for formal accreditation. The UK National External Quality Assessment Scheme (UK NEQAS) for heritable bleeding disorders was established in its current format in 2003, and currently has 27 registered participants in the United Kingdom, the European Union (EU), and the non-EU countries. Two exercises per annum are circulated to participants comprising either whole blood or DNA isolated from cell lines, and laboratories are allowed 6 weeks to analyze the samples and generate a report. Reports are assessed by a panel comprising clinicians and scientists with expertise in this area. Samples to date have involved analysis of the F8 gene (10 exercises), the F9 gene (4 exercises), and the VWF gene (3 exercises) and have comprised a wide spectrum of mutations representing the routine workload encountered in the molecular genetics laboratory. The majority of laboratories in each exercise passed, but a small number did not and reasons for failing included clerical errors, genotyping inaccuracies, and a failure to correctly interpret data. Overall we have seen an improvement in quality of reports submitted for assessment, with a more concise format that will be of value to referring clinicians and counsellors. Informal feedback from participants has been very positive.
Keywords: quality assurance; hemophilia; molecular genetics; mutational analysis